2001
DOI: 10.1128/jcm.39.6.2338-2340.2001
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Aspergillus Species DNA by PCR in Bronchoalveolar Lavage Fluid

Abstract: The usefulness of a nested PCR assay for detection of Aspergillus sp. DNA was evaluated in 177 bronchoalveolar lavage (BAL) fluid specimens. This test was accurate both to diagnose culture-negative BAL fluid specimens from patients with invasive pulmonary aspergillosis and to confirm culture-positive samples. However, it did not differentiate between infection and colonization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
1
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 14 publications
(11 reference statements)
1
38
1
3
Order By: Relevance
“…However, the PPV of this test for diagnosing IPA may be compromised by the fact that it does not distinguish between infection and colonization (Hayette et al, 2001;Raad et al, 2002). This problem may be less when GM detection is used, as was suggested by the high PPV in our study.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…However, the PPV of this test for diagnosing IPA may be compromised by the fact that it does not distinguish between infection and colonization (Hayette et al, 2001;Raad et al, 2002). This problem may be less when GM detection is used, as was suggested by the high PPV in our study.…”
Section: Discussionmentioning
confidence: 65%
“…A number of studies have reported the use of polymerase chain reaction (PCR) in BAL fluid for the diagnosis of IPA (Verweij et al, 1995a;Hayette et al, 2001;Buchheidt et al, 2002;Raad et al, 2002). However, the PPV of this test for diagnosing IPA may be compromised by the fact that it does not distinguish between infection and colonization (Hayette et al, 2001;Raad et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Detection of ASP DNA in BAL fluid theoretically enables early diagnosis and early guided optimal therapy that is expected eventually to improve the outcome of IPA in high-risk patients. [6][7][8][9][10][11] In our hands, the turnaround time for PCR-based detection of aspergillus DNA from BAL sampling until delivery of the results is approximately 1-2 working days, with the molecular diagnostic procedure lasting for about 6 h. This study evaluated the contribution of ASP DNA detection to the diagnostic workup of immune-compromised patients with IPA by comparing the mortality rates during two different time periods, with and without the addition of ASP PCR testing. In-hospital mortality was chosen as the outcome variable, despite the fact that nowadays the disease, especially in allogeneic BMT recipients, can present in the community long after transplantation, because in our hospital the standard of care was to admit patients suspected of having IPA, and treat them in hospital for this diagnosis, even a long time after the BMT.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Early diagnosis of IPA and administration of antifungal treatment is expected to improve outcome, but this goal is difficult to achieve as cultivation of the causative agent Aspergillus species (ASP) from respiratory secretions has poor sensitivity. [3][4][5][6][7] Deep tissue biopsy specimens are difficult to obtain in this setup because many affected patients have poor respiratory status in addition to coagulation defects. PCR-based ASP DNA detection in bronchoalveolar lavage (BAL) fluid theoretically enables earlier and more frequent diagnosis of IPA.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, non-invasive and more reliable techniques are needed to confirm the diagnosis of disease. The use of PCR-based method for identifying Aspergillus-specific DNA, serum and Broncho alveolar lavage (BAL), fluid galactomannan (GM), and antigen assay in ELISA are more favorable options compared to biopsy and culture (6). Moreover, innovative quantitative real-time PCR assay have additionally been built up for IA diagnosis (7).…”
Section: Introductionmentioning
confidence: 99%